Knowledge Level of Futsal Extracurricular Students about Ankle Injuries - Rahmatullah; Ahmad Abdullah; Ardhiyanti Puspita Ratna (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2024)
Futsal is one of the sports that has a high risk factor for ankle injuries. Therefore, futsal sports practitioners should know the prevention and treatment efforts in anticipation of the risk of injury that may occur. The aims of the study was to identify the level of knowledge of students participating in futsal extracurricular activities regarding ankle injuries at Graha Madina Vocational School. This research design is a descriptive quantitative research with a questionnaire survey method via google form. The sampling technique in this study used a total sampling technique so that the research sample was the entire population of 21 students. The analysis technique in this study used descriptive analysis techniques. The instrument used is a questionnaire regarding ankle injuries that has been developed by researcher with the identification of understanding factors, causes of injury, injury prevention, handling, and treatment of ankle injuries. The result of this research analysis shows that students have a level of knowledge in the poor category with an average of 47.62 and details of 17 students (80.96%) have poor knowledge, 4 students (19.04%) have moderate knowledge, and none of the students have good knowledge. The limitation of this study is that the research sample is still classified as a small group scale of 21 students so that further research needs to be done with a larger group scale to get more relevant results.